Nathan the Wise: Dialogue without words - Beyers, Jaco (HTS teologiese studies, 2023)
The ‘dramatic poem’, Nathan der Weise [Nathan the Wise], was written in 1779 by Gotthold Ephraim Lessing in Germany. The scene is set in medieval Jerusalem, where Sultan Saladin rules and where the wealthy merchant Jew, Nathan, lives with his adopted daughter Recha, who is saved from a burning house by a Christian Templar knight. It is clear from the characters that the poem has the making of a fine example of interreligious dialogue. The culmination of the interreligious encounter in the poem is the account of what is now known as the parable of the Three Rings. The principle behind the parable has theological and socio-ethical implications that may guide us in understanding how religions can and ought to engage. This contribution presents a critical reflection of the Three Rings parable to add to the current debate on interreligious relations. The text of the poem is read from a theological socio-ethical perspective. The conclusion drawn from this reflection is that theological reasons may sometimes not be enough to ensure peaceful relations between religions. It may be that religions can together address socio-ethical challenges. Such co-action may transcend theological differences and mitigate interreligious dialogue.Contribution: This contribution wants to critically discuss the dramatic poem ‘Nathan der Weise’ and determine how the Three Rings parable can contribute to current interreligious relations. The research addresses United Nations Sustainable Development Goals numbers 11 and 16, contributing to peaceful co-existence in sustainable communities.